Characteristics of Peripartum Cardiomyopathy (PPCM) pregnancy and preeclampsia in Dr Soetomo Hospital, Surabaya, Indonesia, 2014-2016 - Dibya Arfianda; Budi Wicaksono; Khanisyah Erza Gumilar; Andrianto Andrianto (Universitas Airlangga, 2019)
Objectives: to present data on the characteristics of pregnancy with PPCM and PE. Management of patients with PPCM is almost the same as for patients with acute or chronic heart failure, which uses drug therapy. PPCM and preeclampsia (PE) are two related diseases, although not directly. Both have similar pathophysiological mechanisms.Case Report: We present 25 pregnancy cases with PPCM at Dr. Soetomo Hospital within 3 years. Data were collected from January 2014 to December 2016, consisting of 5 PPCM cases and the other 20 cases were PPCM with PE cases.Conclusion: Pregnancy with PPCM-PE has higher morbidity than PPCM only. The diagnosis of PPCM should be established immediately if heart failure symptoms are found in the third trimester and the patient has risk factors, such as age >30 years, multigravida, obesity, and multiple pregnancy.